MOBILE LEGENDS: BANG BANG - DINAMIKA PERKEMBANGAN GAME MOBILE YANG MEWARNAI GENERASI INDONESIA - Si Ngurah Wahyu Dwi Suputra; I Putu Adi Saskara (Warna Komunikasi, 2025)
Mobile Legends: Bang Bang is a mobile game that has had a major impact on the young generation of Indonesia. Since its release in 2016, the game has grown rapidly and become part of popular culture, supported by increasing smartphone penetration and access to technology. The purpose of this study is to discuss the development of Mobile Legends in three periods: before COVID-19 (2016-2019), during the pandemic (2020-2021), and post-pandemic (2022-2024). This study uses a qualitative approach based on Pierre Bourdieu's theory of social practice. Pierre Bourdieu's theory of social practice, in this study analyzes how Mobile Legends shapes the social structure and cultural identity of the young generation of Indonesia. The concepts of habitus, capital, and arena explain how developers and player communities create social spaces that strengthen norms and cultural interactions in the digital world. As a result, Mobile Legends has a significant economic impact on social structures, opening up new opportunities in the gaming and esports industries and other impacts on Indonesian society.